Examination of Quality Implementation Management for Institutions with Accreditation: An Analysis Study - Jaya, Melinda Puspita Sari; Sinaga, Santa Idayana; Padilah, Padilah; Andriani, Dessi; Natasya, Destri (Gema Wiralodra, 2024)
The purpose of this study is to gather comprehensive data about the quality management analysis of certified institutions in the Kemuning sub-district. The data for this study were gathered by survey methods, which is a qualitative descriptive method. Descriptive analysis is a tool used in data analysis to explain media projects or products and evaluate the outcomes of product feasibility studies. The Bord & Gall model is utilized in the data analysis process, which consists of the following steps: Potential issues should be identified first, then information should be gathered, the product should be designed, validated, revised, and tested. Fifteen The Kemuning sub-district's Early Childhood Teacher Education program has a flexible accreditation cluster that can regulate the caliber of its institutions, ranging from A to accredited status. The work programs that promote ongoing improvement serve as evidence of this.